Microbiologia do solo no ensino médio de Lavras, MG - Vilas Boas, Rogério Custódio (2012)
Microorganisms have relevant functions in the sustainability of ecosystems and for life on the planet, although society is generally not aware of this role and considers only the domain of pathogens. The purpose of this study was to analyze the content about soil microorganisms conveyed to students by biology textbooks of high schools in Lavras, State of Minas Gerais. Students and teachers from three schools of this city were described and the knowledge about soil microbiology of 334 high school students of these schools tested after attractive presentations of the subject in various forms (lectures, workshops and practical classes). The data were collected before and after the presentations by questionnaires and the feasibility of teaching this subject at high school was evaluated as well. Despite the importance of soil microorganisms, the approach of the high school biology textbooks to the subject does not highlight their relevance in the context of agriculture and the environment. After presenting the subject, the comprehension of the students of public and private schools was significantly different. It was found that accessible resources could help teach and improve this content in the subject biology, and that scientific knowledge should be transferred from the universities to high schools.